Expanding sports drug testing assays: Mass spectrometric characterization of the selective androgen receptor modulator drug candidates RAD140 and ACP‐105. (24th April 2013) - Thevis, Mario; Piper, Thomas; Beuck, Simon; Geyer, Hans; Schänzer, Wilhelm
Abstract : RATIONALE: Anabolic agents have been top‐ranked for many years among statistics of adverse analytical findings compiled by the World Anti‐Doping Agency (WADA). Besides archetypical anabolic‐androgenic steroids (AAS), alternative substances with similar effects concerning bone and muscle anabolism have been therapeutically pursued. A prominent emerging class of drugs is the chemically heterogeneous group of selective androgen receptor modulators (SARMs), some of which have been detected in doping control samples between 2009 and 2012 despite missing clinical approval. METHODS: In order to support the momentum of expanding the preventive and proactive measures among anti‐doping laboratories, the analytical characterization of substances with misuse potential is of great importance. In the present study, the SARM drug candidates RAD140 (comprising a 5‐phenyloxadiazole nucleus) and ACP‐105 (bearing an N ‐substituted tropanol pharmacophore) were studied regarding their mass spectrometric behavior under ESI‐MS(/MS) and EI‐MS(/MS) conditions. Reference material was synthesized according to established protocols and dissociation pathways of RAD140 and ACP‐105 were elucidated with liquid chromatography/electrospray ionization quadrupole/time‐of‐flight or iontrap/orbitrap and gas chromatography/electron ionization quadrupole/time‐of‐flight high resolution/high accuracy mass spectrometry. RESULTS: Fragmentation pathways to diagnostic product ions of RAD140 (e.g. m/z 223 and 205 using ESI‐MS/MS and m/z 421 and 349 using EI‐MS/MS) and ACP‐105 (such as m/z 233 and 193 or 231 and 217 for ESI‐MS/MS and EI‐MS/MS measurements, respectively) were proposed as substantiated by determined elemental compositions and MS n experiments as well as comparison to spectra of a structural analog. Notably, for the formation of the characteristic fragment ion at m/z 421 of RAD140, the comparably seldom intramolecular migration of a trimethylsilyl residue triggered by electron ionization was suggested as corroborated by all of the above‐mentioned analytical means. CONCLUSIONS: The obtained data will support future sports drug testing methods and facilitate and accelerate the implementation of this analyte and related compounds or metabolites in both GC/MS(/MS)‐ and LC/MS(/MS)‐based routine doping control procedures. Copyright © 2013 John Wiley & Sons, Ltd.